2012
DOI: 10.1039/c2ib20180a
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytes mediate targeting of iron oxide nanoparticles to tumors for cancer therapy

Abstract: Nanotechnology has great potential to produce novel therapeutic strategies that target malignant cells through the ability of nanoparticles to get access to and be ingested by living cells. However its specificity for accumulation in tumors, which is the key factor that determines its efficacy, has always been a challenge. Here we tested a novel strategy to target and treat ovarian cancer, a representative peritoneal cancer, using iron oxide nanoparticles (IONPs) and an alternating magnetic field (AMF). Perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…19 One explanation for the variable ability of the particles to overcome the peritoneum might be the uptake of SPIOs by peritoneal macrophages, which were not able to cross the peritoneal barrier. This phenomenon has been observed by Toraya-Brown et al 20 Liposomes were able to exit the peritoneal cavity effectively resulting in nearly constant blood liposome levels for a period of several hours. 12,13 In accordance with our results, differences in the biodistribution and pharmacokinetics of nanoparticles depending on their surface characteristics were reported by Chen et al 21 who demonstrated that 188 Re-BMEDA-labeled pegylated liposomes had a 5.3-fold higher terminal half-life in the blood than nonencapsulated 188 Re-BMEDA after IP injection.…”
Section: Discussionmentioning
confidence: 68%
“…19 One explanation for the variable ability of the particles to overcome the peritoneum might be the uptake of SPIOs by peritoneal macrophages, which were not able to cross the peritoneal barrier. This phenomenon has been observed by Toraya-Brown et al 20 Liposomes were able to exit the peritoneal cavity effectively resulting in nearly constant blood liposome levels for a period of several hours. 12,13 In accordance with our results, differences in the biodistribution and pharmacokinetics of nanoparticles depending on their surface characteristics were reported by Chen et al 21 who demonstrated that 188 Re-BMEDA-labeled pegylated liposomes had a 5.3-fold higher terminal half-life in the blood than nonencapsulated 188 Re-BMEDA after IP injection.…”
Section: Discussionmentioning
confidence: 68%
“…49 The 5%-7% of initially injected IONP dose that was found in the tumor in the current study equaled that of a previous study that leveraged tumor-associated peritoneal phagocytes to localize non-targeted IONPs to ovarian tumor masses. 6 It is unclear whether the NSG mouse model of the current study possesses similar tumor-associated peritoneal phagocytes, but the lack of any negative control Bfab-targeted IONPs in the tumor mass might suggest that phagocyte-mediated trafficking of IONPs to the tumor is compromised in the NSG model. If true, we speculate that the use of FOLRα-targeted IONPs in a suitable immuno-competent model might result in additive tumor homing, and such a substantial IONP tumor accumulation would bode well for potential diagnostic and therapeutic applications.…”
mentioning
confidence: 92%
“…8,11 One recent study co-opted tumor-associated peritoneal phagocytes to selectively deliver IONPs in an ovarian cancer model. 6 In other work, luteinizing hormone-releasing hormone (LHRH) peptide was used as an IONP-targeting moiety for ovarian cancer cells overexpressing the LHRH receptor. 12 Similarly, many ovarian cancers overexpress folate receptor alpha (FOLRα), 13,14 and this fact has been leveraged to selectively construction of Ffab and anti-botulinum toxin fab fragments…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, the high hydrophobicity and slow-degradation property of PLGA also limit its application in human body [18]. D-a-tocopheryl polyethylene glycol 1000 succinate (TPGS) is a water-soluble PEG derivative of natural-source vitamin E with an amphiphilic structure which comprised of a hydrophilic polar head group (polyethylene glycol, PEG) and a lipophilic alkyl tail (tocopherol succinate) [15,19]. By introducing TPGS to PLGA, we can overcome these shortcomings [20,21].…”
Section: Introductionmentioning
confidence: 99%